2021
DOI: 10.1073/pnas.2114937118
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule sequencing reveals a large population of long cell-free DNA molecules in maternal plasma

Abstract: In the field of circulating cell-free DNA, most of the studies have focused on short DNA molecules (e.g., <500 bp). The existence of long cell-free DNA molecules has been poorly explored. In this study, we demonstrated that single-molecule real-time sequencing allowed us to detect and analyze a substantial proportion of long DNA molecules from both fetal and maternal sources in maternal plasma. Such molecules were beyond the size detection limits of short-read sequencing technologies. The proportions of lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
74
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 39 publications
0
74
0
Order By: Relevance
“…In this respect, an obvious distinction should be posed between: (1) neurodevelopmental aberrancies occurring during the first half of gestation and (2) later pathogenic phenomena (e.g., altered maturation schedule of astroglia and oligodendroglia, abnormal shaping of dendritic trees and misregulation of neuron activity/excitability), taking place during later gestational life as well as after birth. Despite recent advancements in experimental prenatal diagnosis of fetal mutations [35,36], due to their extremely early occurrence, the former will be hardly tractable. Conversely, as for the latter, the availability of a standardized platform for fast multidimensional profiling of novel mutant alleles (such as the one described here), could pave the way to timely therapeutic interventions, eventually resulting in an appreciable mitigation of the corresponding neurological symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, an obvious distinction should be posed between: (1) neurodevelopmental aberrancies occurring during the first half of gestation and (2) later pathogenic phenomena (e.g., altered maturation schedule of astroglia and oligodendroglia, abnormal shaping of dendritic trees and misregulation of neuron activity/excitability), taking place during later gestational life as well as after birth. Despite recent advancements in experimental prenatal diagnosis of fetal mutations [35,36], due to their extremely early occurrence, the former will be hardly tractable. Conversely, as for the latter, the availability of a standardized platform for fast multidimensional profiling of novel mutant alleles (such as the one described here), could pave the way to timely therapeutic interventions, eventually resulting in an appreciable mitigation of the corresponding neurological symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we found that in our families, rs635299 was informative in only 25% of cases. The latest study on NIPD for single gene disorders 22 concerned testing for FXS in a single family. A conclusive result was obtained from the analysis of three fetal DNA molecules, two of which carried recombinant events.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are encouraging in view of the rare published data on NIPD for dynamic mutations based on the analysis of circulating DNA: three indirect studies of the transmission of the paternal morbid allele 20,21 and two direct studies of two families at risk of maternal transmission 10,22 . The first three papers describe an indirect method that does not allow NIPD if the carrier parent is the mother.…”
Section: Discussionmentioning
confidence: 99%
“…Longer cfDNA fragments have not been extensively studied due to limitations of short-read technology, and these could be valuable both for biomarker discovery and the basic biology of cfDNA (i.e. ( 19 )).…”
Section: Discussionmentioning
confidence: 99%
“…ONT has primarily been used for long-read sequencing, but recent work by our group and others has shown that it can be adapted for short fragments without additional processing steps (16)(17)(18). As an added benefit, the ability to capture much longer cfDNA fragments than shortread sequencing may lead to new discoveries or biomarkers, as was demonstrated recently in the case of longer fragments during pregnancy (19).…”
Section: Introductionmentioning
confidence: 99%